2013
DOI: 10.1371/journal.pone.0068268
|View full text |Cite
|
Sign up to set email alerts
|

Excess of Methyl Donor in the Perinatal Period Reduces Postnatal Leptin Secretion in Rat and Interacts with the Effect of Protein Content in Diet

Abstract: Methionine, folic acid, betaine and choline interact in the one-carbon metabolism which provides methyl groups for methylation reactions. An optimal intake of these nutrients during pregnancy is required for successful completion of fetal development and evidence is growing that they could be involved in metabolic long-term programming. However, the biological pathways involved in the action of these nutrients are still poorly known. This study investigated the interaction between methyl donors and protein con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 52 publications
4
35
1
Order By: Relevance
“…In this study, we provide the evidence that maternal betaine supplementation across gestation and lactation exerts distinct effects on growth in F1 and F2 offspring. F1 showed a retarded growth and decreased body weight, which is in line with a previous finding that an excess methyl donor in the perinatal period significantly reduced the body weight of female rat offspring . However, other investigators reported conflicting results that methyl donor supplementation increased the fetal weight and birth weight in pigs, whereas maternal methyl donor restriction decreased the birth weight in rats .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In this study, we provide the evidence that maternal betaine supplementation across gestation and lactation exerts distinct effects on growth in F1 and F2 offspring. F1 showed a retarded growth and decreased body weight, which is in line with a previous finding that an excess methyl donor in the perinatal period significantly reduced the body weight of female rat offspring . However, other investigators reported conflicting results that methyl donor supplementation increased the fetal weight and birth weight in pigs, whereas maternal methyl donor restriction decreased the birth weight in rats .…”
Section: Discussionsupporting
confidence: 86%
“…Additionally, we observed significantly increased F1 litter size and litter weight in betaine‐supplemented group. Again, this is against the previous reports that maternal methyl donor supplementation or restriction did not affect the litter size in pigs , but reduced litter size in rats . These inconsistent findings may be explained by differences in the types and levels of methyl donors, the time and period of supplementation, as well as the animal species and diet compositions.…”
Section: Discussioncontrasting
confidence: 79%
“…HF feeding during murine gestation led to greater food intake and weight gain, and DNA hypomethylation in the prefrontal cortex of offspring, whereas methyl donor supplementation [including choline] attenuated these alterations [31]. Methyl donor supplementation during the perinatal period reduced leptin secretion in rat offspring [32], while supplementing methyl donors to HF-fed or high-fat-sucrose-fed dams protected offspring from increased weight gain [33], adiposity [33], and steatosis [34]. In addition to its role as a methyl donor, choline is also a lipotropic factor that facilitates lipid export from the liver by serving as an essential component on the VLDL membrane.…”
Section: Discussionmentioning
confidence: 99%
“…This result is in line with a previous finding that an excess methyl donor supplementation in the perinatal period reduces the body weight of female rat offspring. [ 27 ] Interestingly, we found that betaine supplementation in F0 dams increased the birth weight and weaning weight of F2 offspring. Similar transgenerational inheritance effects were observed during Dutch famine period.…”
Section: Discussionmentioning
confidence: 87%